Basic Principles Of Sulfide Smelting And Converting With Oxygen-Rich Gas - Kimio Itagaki (The Minerals, Metals and Materials Society, 2002)
Thermodynamics and rate process fundamentals are two of the important principles involved in nonferrous production processes. The process configuration establishes whether thermodynamics or rate process behavior is most relevant in a particular application. In this paper, thermodynamic theory and rate process fundamentals are used to analyze the main characteristics of smelting and converting processes. The effect of increased oxygen potential .is examined with emphasis in view of the increased use of highly oxygen-enriched gas in modem smelting processes. Phase equilibrium and the distribution of minor elements between copper or nickel matte and FeOx-SO2- or FeOx-CaO-based slag are reviewed. The use of oxygen-rich gas has no serious effects on 'the recovery of valuable copper and silver in the matte phase, while the recovery of nickel and cobalt is adversely affected. The oxygen content in the gas also strongly affects the distribution behavior of arsenic, antimony and bismuth. Analysis of the rate processes occurring in the shaft of flash smelting, and converting furnaces by a 3-D computational fluid-dynamics model is also discussed. After being validated with experimental data collected in a large laboratory furnace, the computer model has been used to simulate the main features of an industrial flash converting operation. The results present quantitative features of the improved mixing of the particle-gas suspension and increased oxygen efficiency obtained with a distributor-cone burner compared with those with a single axial entry burner. The role of basic principles in the engineering analysis of high-intensity matte smelting processes is also discussed.